Work Environment And Corporate Culture Influence On The Performance Of Employees Of Pt. Tiga Serangkai Pustaka Mandiri - Oraibi, Khaled Omar Mohamed, Drs. M. Farid Wajdi, M.M Ph.D, Drs. Ahmad Mardalis, MBA (2015)
The purpose of this study are: first, to Determine the influence of the work environment on the performance of employees in the company; second, to Determine the influence of corporate culture on the performance of employees in the company; third, to Determine the influence of the working environment and corporate culture on the performance of employees in the company. This research is quantitative, by taking samples at PT. Tiga Serangkai Pustaka Mandiri, Surakarta, Indonesia. The study population and sample as many as 268 employees were taken by 100 employees. The technique of collecting data using questionnaires. The data analysis technique used is multiple linear regression analysis. The results obtained showed that: first, there is a positive and significant contribution of the work environment on employee performance at PT. Tiga Serangkai Pustaka Mandiri; second, there is a positive and significant contribution of the corporate culture on employee performance at PT. Tiga Serangkai Pustaka Mandiri; third, there is a positive and significant contribution of the work environment and corporate culture on employee performance at PT. Tiga Serangkai Pustaka Mandiri.